Earth Day Issue Editorial: Vol 09 No 01 - Grossman, Alyssa; Kamerling, Leonard J.; Thorsen, Åshild Sunde Feyling; Gan, Gregory; Dietrich, Martha-Cecilia (Journal of Anthropological Films, 2025)
The release of our first 2025 issue on 22 April, coordinated by our new editorial team, coincides with Earth Day 2025. This issue presents five films that take a close look at natural resource extraction worldwide, including gold, copper, oil, sand and stone. The films were not prompted by a specific call but emerged as a common theme from the submissions we received, reflecting a shared spectrum of concerns engaging anthropologists and filmmakers today. In our contemporary era that is profoundly characterised by anthropogenic environmental impact, these films highlight the social inequalities and power imbalances affecting the global majority, causing certain populations to experience the effects of environmental harm more directly and acutely than others. However, the films featured here do not portray such communities as passive victims; rather, they illuminate people’s creative and impassioned forms of resistance, their drive to educate and mobilise against these larger forces, and their assertion of their own rights and agency while fighting for a fundamental sense of respect and accountability towards the natural world we all share.